Synthesis and antibacterial activities of some new arenesulfonamides and urea derivatives - (:unkn) unknown (My University, 1996)
Reactions of 3-substituted-4-amino-4,5-dihydro-1H-1,2,4-triazol-5-ones [I] with some arenesulfonyl chlorides and aryl isocyanates were studied and the corresponding N-(3-substituted-4,5-dihydro-1H-1,2,4-triazol-5-one-4-yl) arenesulfonamides [II-VI] and N-aryl-N-(3-substituted-4,5-dihydro-1H-1,2,4-triazol-5-one-4-yl) ureas [V, VI] were obtained. The structural assignments of new 19 compounds are based on spectral data and elemental analysis. Furthermore, compounds II-VI were tested for their in vitro antimicrobial activities.
Keywords: 4,5-dihydro-1H-1,2,4-triazol-5-ones; Antibacterial actvity; Arenesulfonamides; Synthesis; Ureas